FLUKTUASI KINERJA KEUANGAN PERBANKAN SYARIAH: ANALISIS PADA IMPLEMENTASI PROFIT LOSS SHARING DAN MANAJEMEN RISIKO - Fajar, Maulana; Kusuma, Triana Hasty; Yuliana, Novita; Ratnawati, Dwi Puji (Jurnal Studi Manajemen Bisnis, 2023)
Profit Loss Sharing (PLS) plays a crucial role in determining the potential value of profits in Islamic banking. The PLS profit-sharing system indicates the success or failure in the financing investments undertaken by the banks. To generate profits from the financing investments, it is essential to have a reliable and sustainable risk management. In this study, the risk management variable will be comprehensively examined in relation to its impact on supporting the implementation of PLS systems (mudharabah and musyarakah) on financial performance. The analytical method employed is quantitative analysis with the support of the E-Views application program. The research sample includes 11 Islamic commercial banks in Indonesia, with an observation period from 2017 to 2022. The research analysis results demonstrate that mudharabah financing and musyarakah financing have a positive influence on financial performance. Risk management weakens the influence of mudharabah financing and musyarakah financing on financial performance. In terms of direct influence, risk management exerts the strongest impact compared to mudharabah financing and musyarakah financing. Mudharabah financing has the smallest impact on the value of financial performance.